ASSOCIATION OF RENAL AGENESIS AND IPSILATERAL SEMINAL VESICLE CYST – ARARE CASE OF ZINNER SYNDROME - Chalcheska, Slavica; Jovanoska, Ivona; Dejanova Panev, Sandra; Veljanovski, Dimitar; Nancheva Bogoevska, Andrea (Македонско лекарско друштво = Macedonian medical association, 2023)
Introduction We report a case of Zinner syndrome, a congenital malformation characterized by association of renal agenesis, ipsilateral seminal vesicle cyst and ipsilateral ejaculatory duct obstruction. Case presentation A 44 years old patient, previously diagnosed with benign prostatic hyperplasia and chronic prostatitis was admitted at our department for puncture of pelvic cyst. Transrectal ultrasound (US) guided puncture and aspiration of the cyst was performed. Few days later, patient presented with septic symptoms and computed tomography (CT) scan was done, which showed large cyst with air inclusions, measuring 13x14cm in diameter in right seminal vesicles and right renal agenesis compatible with Zinner syndrome. An urgent surgical drainage of the cyst was done, followed by improvement of patient’s clinical condition. Discussion Zinner syndrome is one of the rarest congenital anomalies of urogenital tract and is usually discovered and diagnosed after3rd -4th decade of life. Patients are often asymptomatic but they can present with dysuria, recurrent prostatitis or epdidymitis. Radiological modalities have a significant role into detecting and evaluating Zinner syndrome including US, CT and MRI. When symptomatic, most commonly due to its size, surgical excision or transrectal aspirations of the cyst are options of treatment. Conclusion Combination of clinical history and radiological imaging are essential for making the diagnosis and proper management of this rare entity.